Cloning and expression of the Lactobacillus fermentum acid urease gene in Saccharomyces cerevisiae - Visser, Johanna Jacoba (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1999.